EKSISTENSI PEMUDA MUHAMMADIYAH DALAM MENINGKATKAN AQIDAH MASYARAKAT DI JOGOKARIYAN PADA TAHUN 1965-1999 - Endah Dwi Sulistyani, Fatimah; Siswanta (Universitas PGRI Yogyakarta, 2022)
This research aims to determine the existence of Muhammadiyah youth in improving the faith of the Jogokariyan community, namely: (1) Muhammadiyah Youth's da'wah methods in improving the aqidah of the Jogokariyan community, (2) The development influence of Muhammadiyah Youth reform movement in Jogokariyan Village, (3) Hurdles and solutions of Muhammadiyah Youth in improving community aqidah in Jogokariyan Village. The research was conducted in Jogokariyan village using qualitative research methods with a narrative approach. The data was collected by doing interviews and direct observation of religious activities in Jogokariyan village, the data sources came from informants who were directly involved in Muhammadiyah youth organizations and the local community. The data in this research is analyze by triangulation and drawing conclusions. The results of the study concluded that: (1) the da'wah methods used by Muhammadiyah youth in the Jogokariyan village were (a) The Hizbul Wathan (HW) movement, (b) Tapak Suci martial art training, (c) activities such as recitation of the Quran, (d) sports activities, (e) healthy walks and (f) social service activities. (2) Muhammadiyah Youth is the driving force of every religious activity carried out in Jogokariyan Village. Jogokariyan Mosque is theheadquarters of the movement and have influences on the development of movement renewal in Muhammadiyah Village. (3) the obstacles of Muhammadiyah Youth in improving aqidah in Jogokariyan Village were: lack of understanding of Islam because kejawen culture is still strongly believed and there are so many people whoracticed the tradition of gambling and drinking alcohol. That was some reasons that became obstacles for Muhammadiyah Youth at that time. The solution to this problem is to improve the performance of Muhammadiyah Youth to be more creative and innovative so that they can keep up with this technological era so they don't left behind from others.